Employment discrimination law [compact disc] : problems, cases and critical perspectives - McDonald, Janis (Janis L.); Ravitch, Frank S., 1966-; Sumners, Pamela (Upper Saddle River, NJ : Pearson/Prentice Hall, 2006)
01